Identification of Bone Skeleton in Old Well - Nugroho, Novianto Adi (Smart Medical Journal, 2022)
The purpose of forensic identification of cadavers is to identify each bone's usefulness in the identification process in addition to establishing the time and cause of death. Identification of skeletonized corpses will be difficult to assess, and pathological conditions such as broken bones and bruising of the bones are also an assessment of signs of violence in the individual. The results of the examination of the human skeleton show that one individual was identified. Meanwhile, bone is a mongoloid male, estimated to be between 20-25 years old with a bone height of 159 - 166 cm, in which bruises were found on top of the head. Post-mortem fractures were found at the tip of the distal femur and proximal tibia, and the estimated time of death is more than three months. The assessment of diatoms in the upper arm bones, which yielded a negative result, was done as a supporting investigation. Further, a sample of DNA was extracted from one of the second right ribs for analysis.